D’hier à aujourd’hui : les premiers lieux d’inhumation des musulmans à Paris et à Londres (1857-2017) - Nada Afiouni (Revue Française de Civilisation Britannique)
This article provides a twofold comparative analysis. Firstly, it explores the complex historical and political contexts underlying the creation of Muslim-specific funerary allotments in Paris and London in the early 19th century. Secondly, it examines the rationale behind 21st century public programmes rehabilitating these cemeteries. The study shows that these projects, each embedded in its own broader public political discourse on cultural and religious plurality, served the same aim in both countries; the memorialisation of these Muslim cemeteries were responses to the need for an inclusive heritage. Four cemeteries are examined, those in Bobigny and Père Lachaise in Paris and those in Brookwood and Woking in the Greater London Area. These aggregations of graves were the first to be identified as specifically Muslim in both capitals. The study incorporates the findings of archive work conducted in the London Muslim Centre Archive collections, semi-structured interviews with municipal agents in Woking as well as field observation (2017-2018).